Digital Health Care in Taiwan Innovations of National Health Insurance - Lee, Po-Chang; Wang, Joyce Tsung-Hsi; Chen, Tzu-Yu; Peng, Chia-hui (Springer Nature, 2022)
This open access book introduces the National Health Insurance (NHI) system of Taiwan with a particular emphasis on its application of digital technology to improve healthcare access and quality. The authors explicate how Taiwan integrates its strong Information and Communications Technology (ICT) industry with 5G to construct an information system that facilitates medical information exchange, collects data for planning and research, refines medical claims review procedures and even assists in fighting COVID-19. Taiwan's NHI, launched in 1995, is a single-payer system funded primarily through payroll-based premiums. It covers all citizens and foreign residents with the same comprehensive benefits without the long waiting times seen in other single-payer systems. Though premium rate adjustment and various reforms were carried out in 2010, the NHI finds itself at a crossroads over its financial stability. With the advancement of technologies and an aging population, it faces challenges of expanding coverage to newly developed treatments and diagnosis methods and applying the latest innovations to deliver telemedicine and more patient-centered services. The NHI, like the national health systems of other countries, also needs to address the privacy concerns of the personal health data it collects and the issues regarding opening this data for research or commercial use. In this book, the 12 chapters cover the history, characteristics, current status, innovations and future reform plans of the NHI in the digital era. Topics explored include: Income Strategy Payment Structure Pursuing Health Equity Infrastructure of the Medical Information System Innovative Applications of the Medical Information Applications of Big Data and Artificial Intelligence Digital Health Care in Taiwan is essential reading for academic researchers and students in healthcare administration, health policy, health systems research, and health services delivery, as well as policymakers and public officials in relevant government departments. It also would appeal to academics, practitioners, and other professionals in public health, health sciences, social welfare, and health and biotechnology law.